2016
DOI: 10.1063/1.4959144
|View full text |Cite
|
Sign up to set email alerts
|

Large magnetoresistance in Heusler-alloy-based epitaxial magnetic junctions with semiconducting Cu(In0.8Ga0.2)Se2 spacer

Abstract: We investigated the structure and magneto-transport properties of magnetic junctions using a Co 2 Fe(Ga 0.5 Ge 0.5) Heusler alloy as ferromagnetic electrodes and a Cu(In 0.8 Ga 0.2)Se 2 (CIGS) semiconductor as spacers. Owing to the semiconducting nature of the CIGS spacer, large magnetoresistance (MR) ratios of 40% at room temperature and 100% at 8 K were obtained for low resistance-area product (RA) values between 0.3 and 3 X lm 2. Transmission electron microscopy observations confirmed the fully epitaxial gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…Thanks to the coherent spin-polarized tunneling, the observed MR ratio is several times higher than those reported in MTJs consisting of polycrystalline FM electrodes with an amorphous GaO x barrier (at most ~22% at RT) [22,23,24]. This is the highest value among the reported MTJs with a SC barrier at RT [14,15,22,23,24,25,26,27,28,29,30,31]. It was found in the fully epitaxial MTJs that the growth of a few monoatomic (ML; 1 ML = 0.21 nm) MgO(001) underlying layers on the Fe(001) bottom electrode are indispensable to realize a high MR ratio and that a tunneling MR (TMR) effect cannot be observed without the MgO underlying layer.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Thanks to the coherent spin-polarized tunneling, the observed MR ratio is several times higher than those reported in MTJs consisting of polycrystalline FM electrodes with an amorphous GaO x barrier (at most ~22% at RT) [22,23,24]. This is the highest value among the reported MTJs with a SC barrier at RT [14,15,22,23,24,25,26,27,28,29,30,31]. It was found in the fully epitaxial MTJs that the growth of a few monoatomic (ML; 1 ML = 0.21 nm) MgO(001) underlying layers on the Fe(001) bottom electrode are indispensable to realize a high MR ratio and that a tunneling MR (TMR) effect cannot be observed without the MgO underlying layer.…”
Section: Introductionmentioning
confidence: 88%
“…Semiconductors (SC) have great potential as the tunnel-barrier of MTJ for a low resistance-area product [14,15] because of its rather narrow band-gap, compared with insulators. Also, fully single-crystalline FM/SC/FM structure is one of the important building blocks of a vertical-type spin field-effect-transistor having nonvolatile memory functionality [16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work 9) , we theoretically studied spin-dependent transport properties of two MTJs with different semiconductor barriers, CuInSe2 (CIS) and CuGaSe2 (CGS), to understand the origin of the high MR ratios observed in the CIGS-based MTJs 8) . By analyzing their complex band structures and k// dependences of the transmittances, we found that spin-dependent coherent transport of Δ1 wave functions occurs in both the CIS-and CGS-based MTJs, which can explain the high MR ratios in the CIGS-based MTJs.…”
Section: Introductionmentioning
confidence: 99%
“…1) New tunnel-barrier materials, such as spinel Mg-Al-O(001), and new ferromagnetic materials, such as Heusler alloys, [12][13][14][15][16][17] may outperform the MgO barrier and CoFeB electrodes in the near future. For an MTJ composed of such new materials to exhibit high performance, it must be epitaxially grown on a single-crystal substrate.…”
mentioning
confidence: 99%